A review on readiness of non-Malay youth in joining Malaysian Armed Forces - Dahalan, Dzuhailmi; Ismail, Ismi Arif; D’Silva, Jeffrey Lawrence; Samah, Asnarulkhadi Abu; Kamarudin, Nurul Akhtar (Human Resource Management Academic Research Society, 2023)
The Malaysia Armed Forces have historically been dominated by Malay personnel, with limited representation from non-Malay communities. However, recent years have seen a growing interest among non-Malay youth in joining the armed forces and contributing to national defense. This review aims to synthesize the existing literature on the readiness of non-Malay youth to join the Malaysia Armed Forces and identify the factors that influence their decision. The review examines a range of studies that have investigated the topic of nonMalay youth's readiness to join the armed forces, including both quantitative and qualitative studies. The studies suggest that while there is a willingness among non-Malay youth to join the armed forces, they face various barriers and challenges that limit their participation. These barriers include a lack of awareness and information about military careers, cultural and linguistic barriers, and perceptions of discrimination and unequal treatment within the armed forces. The review also identifies several factors that influence non-Malay youth's readiness to join the armed forces, such as family support, positive perceptions of the military, and the availability of career opportunities within the armed forces. The review highlights the need for efforts to increase awareness and information about military careers among nonMalay communities, address issues of discrimination and unequal treatment within the armed forces and create a more inclusive and diverse armed forces that reflects Malaysia's multi-ethnic society. In conclusion, this review contributes to a better understanding of the readiness of non-Malay youth to join the Malaysia Armed Forces and the factors that influence their decision. It also highlights the importance of promoting diversity and inclusivity within the armed forces, which is crucial for building a strong and unified national defense.